Uji diagnostik uji antigen sars-cov-2 pada pemeriksaan laboratorium covid-19: Studi kasus di RS Beriman Kota Balikpapan, Indonesia - Dwi Hartantoro; Anik Nuryati; Siti Nuryani (PUINOVAKESMAS, 2021)
The performance characteristics of the rapid SARS-CoV-2 antigen detection test should be evaluated and compared with the reverse transcription-polymerase chain reaction (RT-PCR) assay as the standard for diagnosis of COVID-19 cases. This research is a descriptive observational study with a cross-sectional research design. Secondary data from suspected COVID-19 patients who were examined for SARS-CoV-2 antigen and the results of RT-PCR in January - April 2021 at the Beriman Hospital of Balikpapan City, which was 336 samples. Based on the results of the study, the number of samples with an antigen-positive test for SARS-CoV-2 and a positive RT-PCR result was 114 (33.93%), the number of samples with an antigen-positive test for SARS-CoV-2 and a negative RT-PCR result was 2 (0.6%), the number of samples with positive SARS-CoV-2 antigen-negative test results and RT-PCR was 23 (6.85%), and the number of samples with SARS-negative antigen-negative test and RT-PCR results CoV -2 and negative PCR were 197 (58.63%). The result of the SARS-CoV-2 antigen sensitivity was 83.21%, while the specificity was 98.99%. The accuracy value of the SARS-CoV-2 antigen is 92.56%. The rapid antigen test used in this study has sensitivity and specificity as recommended by WHO, so it is suitable for use for COVID-19 laboratory tests.